Film narratives as public relations in Hollywood-China soft power rivalry - Suprapto, Deddy; Sjoraida, Diah Fatma; Salam, Syahrul (ProTVF, 2026)
Background: Film has been playing more of the role as a symbolic tool for public relations to externalize countries’ soft power and nationalism in such geo-political competition among major countries in world communication. Purpose: This study aims to analyse how these filmic narratives function as public relations texts within the sphere of soft power competition between Hollywood and Chinese cinema through an analysis of both the ideological meaning and cultural significance constructed around these personalities, figures, and ideas on a global scale. Methods: Drawing on the qualitative comparative case study methodology and a media political economy model, this study examines theme narratives of certain Hollywood and Chinese films that depict representations of national identity and geopolitical interests along three dimensions; (a) literary narrative, (b) censorship laws, and (c) capitalist structure of media. Results: I find that Hollywood films promote a narrative of global leadership, technological advancement and liberal values in the context of what I call “entertainment capitalism”, while Chinese movies emphasize nationalism, state ideology and reinterpreting history under conditions of “state capitalism” with severe media regulation. Conclusion: In both cases, film narratives work as symbolic public relations rather than institutional ones that frame these forms of soft-power competition between Hollywood and China Implications: The study emphasizes the value of storytelling in film that changes as the experiential space is utilized for public diplomacy; here, it promises contributions to theorization in film studies, cultural diplomacy and international communication research.